Family as the Front Guard: Strategy For Preventing Violence Against Children From the Perspective of Law No. 35 Of 2014 on Child Protection - Nahyu Amalya; Tri Eka Putra Muhtarivansyah Waruwu (SEAN Institute, 2025)
This study discusses in depth the role of the family in preventing violence against children from the perspective of Law No. 35 of 2014 concerning Child Protection, and offers applicable and law-based strategy solutions. Violence against children is a violation of human rights that has long-term impacts on the psychological, social, and physical development of children. In this context, Law No. 35 of 2014 concerning Child Protection emphasizes the role of the family as the front line in preventing violence against children. This study aims to examine preventive strategies that can be adopted by families in preventing violence against children, in accordance with the principles of child protection mandated in the law. A juridical-normative approach is used to analyze legal provisions and their implementation at the family level. The results of the study indicate that active involvement of parents in positive parenting, education of anti-violence values, and increasing legal awareness are the main strategies in protecting children in the domestic environment. The family not only functions as the first social unit, but also as the main fortress in guaranteeing children's rights to a sense of security and protection from all forms of violence.